2020
DOI: 10.3390/pr8070800
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Oil Hydrocarbons and Kerogen Destruction of Carbonate–Siliceous Domanic Shale Rock in Sub- and Supercritical Water

Abstract: This paper discusses the results of the influences of subcritical (T = 320 °C; P = 17 MPa) and supercritical water (T = 374 °C; P = 24.6 MPa) on the yield and composition of oil hydrocarbons generated from carbonaceous–siliceous Domanic shale rocks with total organic content (Corg) of 7.07%. It was revealed that the treatment of the given shale rock in sub- and supercritical water environments resulted in the decrease of oil content due to the intensive gas formation. The content of light hydrocarbon f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…The results of the investigation justify the correspondence of hydrocarbon fluids to a single genetic series and its connection with sapropel matter of marine genesis [33,39,40]. The hydrocarbon composition of shale oil after hydrothermal treatment becomes similar to the shale oil produced by PJSC Tatneft from low-permeable carbonate rocks of the Dankovo-Lebedyan horizon of the Bavlinsky reservoir [14,57,58], which is located in the east of Tatarstan.…”
Section: Zelenogorskaya Area Berezovskaya Areamentioning
confidence: 52%
See 1 more Smart Citation
“…The results of the investigation justify the correspondence of hydrocarbon fluids to a single genetic series and its connection with sapropel matter of marine genesis [33,39,40]. The hydrocarbon composition of shale oil after hydrothermal treatment becomes similar to the shale oil produced by PJSC Tatneft from low-permeable carbonate rocks of the Dankovo-Lebedyan horizon of the Bavlinsky reservoir [14,57,58], which is located in the east of Tatarstan.…”
Section: Zelenogorskaya Area Berezovskaya Areamentioning
confidence: 52%
“…The significant part of OM corresponds to the bituminous resins and asphaltenes, and kerogen, which is considered one of the petroleum sources. However, the transformation of kerogen into the hydrocarbons occurs at a temperature above 100 • C [12][13][14][15][16][17]. Thus, the thermal methods, which are applied for the development of Domanic deposits, provide catagenic transformation of organic matters in a certain degree [8].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have found that steam flooding of heavy oil and oil-saturated rocks results in the destruction of the weakest carbon-heteroatom bonds with detachment of peripheral fragments from resins and asphaltenes and formation of lighter hydrocarbons [1][2][3][4][5][6][7][8][9][10][11]. The destruction of asphaltenes under the steam treatment occurs primarily through the weak aliphatic sulfide bonds ( Figure 1) that are destabilized by electron-withdrawing functional groups.…”
Section: Catalytic Aquathermolysismentioning
confidence: 99%
“…The authors proposed the catalytic role of metal ions in the aquathermolysis process. Since then, substantial advances in catalysis have made the catalytic aquathermolysis a distinct process, and catalytic steam-based heavy oil recovery techniques has been investigated as a promising technology to recover heavy oil resources [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. More importantly, this process occurs in the cheapest high-pressure reactor of all, petroleum formations [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“… 26 Nasyrova et al studied the effects of subcritical and supercritical water on the generation of hydrocarbons from Domanic shale rocks and showed that the yields of light hydrocarbons (saturated and aromatic hydrocarbons) in the shale oil increased from 33.98% to 39.63% and 48.24%, respectively. 27 …”
Section: Introductionmentioning
confidence: 99%